SOSIALISASI PARENTING: STRATEGI DAN PERSIAPAN MEMILIH SEKOLAH KE JENJANG SELANJUTNYA: RA PERMATA HATI, PAGENTAN, KECAMATAN SINGOSARI - Hadi, Dj Tekhen Hadi Pramudya (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2025)
Parenting socialization is a strategic step in supporting optimal early childhood development, especially in the aspects of physical, emotional, focus ability, and social interaction. This activity aims to increase parents' understanding of their roles and responsibilities in educating children in the home environment. The socialization program was held at Permata Hati Kindergarten, Pagentan, Singosari, Malang, involving 58 participants consisting of 55 women and 3 men, aged between 25 and 45 years. The materials presented included guidance on choosing the right school, effective communication techniques, emotional management, educational games that train children's focus and motor skills, and learning strategies that are fun and in accordance with the child's developmental stage. Through this activity, parents gained knowledge to choose educational institutions that match their children's interests and potential, manage emotions positively, monitor children's growth and development holistically, and strengthen the synergy between the role of family and school institutions in creating a conducive and supportive learning environment for children.